Is the Time of Emancipation Over? - Rancière, Jacques (Filozofski vestnik, 2016)
The change in our intellectual landscape since the times of the turbulent sixties is exemplified by the word ‘end’. However, the end of the promises of history brought about the recycling of certain elements of Marxist critical discourse, even though their meaning has been reversed: in contemporary intellectual counterrevolution, economic necessity, the critique of democracy and the rights of Man, and the theory of ideological inversion phrase the configuration of the world prescribed by the dominant powers. This situation obliges us to rethink what emancipation actually means, proceeding from the affirmation of the capacity to think and act as the capacity of anyone. Above all, it obliges us to reflect upon its temporality.